PEMBERDAYAAN MASYARAKAT MELALUI PENINGKATAN ATRAKSI WISATA BUDAYA DAN PRODUK KULINER LOKAL DI DESA PENIWEN, MALANG - Hari Minantyo; Thomas S Kaihatu; Devina Irtanto; I Dewa Gde Satrya (Jurnal Terapan Abdimas, 2026)
Abstract. Peniwen Village, located in Kromengan Sub-district, Malang Regency, East Java province, through its tourism awareness group (Pokdarwis Gesang Selaras), possesses a unique cultural tourism potential rooted in the Christian of Jawi Wetan tradition (GKJW / Gereja Kristen Jawi Wetan), which is rarely found in other regions. However, this potential has not yet been optimally managed, both in terms of cultural attraction management and supporting product development. This community service program applied a participatory action research approach through training, mentoring, and hands-on practice with members of Pokdarwis and local villagers. The implication of this activity is the learning experience of the Peniwen Tourism Village community in increasing their insight and skills for the progress of the village. The activities consisted of: (1) strengthening the management capacity of cultural village tourism based on the Christian of Jawi Wetan tradition through workshops and simulations of cultural attraction management, and (2) conducting training on local food processing innovations to produce three value-added new products such as shredded meat (abon), dumplings (siomay), and jerky (dendeng) as complementary attractions and entrepreneurial opportunities. The results indicated an improvement in the capacity of Pokdarwis to design cultural tourism attractions that are more systematic, engaging, and educational for visitors with measurable indicators, namely the creation of a more effective travel pattern for cultural tourism in Peniwen Village. Furthermore, the community successfully developed innovative local food products with higher economic value and potential as signature souvenirs of Peniwen Village. This program not only reinforced the villages cultural identity but also created opportunities for economic diversification through the synergy of cultural tourism and local product development.   Abstrak. Desa Peniwen, Kecamatan Kromengan, Kabupaten Malang, Propinsi Jawa Timur, melalui Pokdarwis Gesang Selaras, memiliki potensi wisata budaya yang unik karena berbasis pada tradisi religi Kristen Jawi Wetan (GKJW / Gereja Kristen Jawi Wetan) yang jarang ditemui di daerah lain. Namun, pengelolaan potensi ini belum optimal, baik dalam manajemen atraksi budaya maupun dalam pengembangan produk pendukung pariwisata. Kegiatan pengabdian masyarakat ini menggunakan pendekatan participatory dengan metode pelatihan, pendampingan, dan praktek langsung bersama anggota Pokdarwis dan masyarakat desa. Nilai implikatif dari kegiatan ini adalah, pengalaman pembelajaran masyarakat Desa Wisata Peniwen dalam meningkatkan wawasan dan keterampilan diri mereka untuk kemajuan desa. Tahapan kegiatan meliputi: (1) penguatan kapasitas manajemen desa wisata melalui workshop dan simulasi pengelolaan atraksi budaya; serta (2) pelatihan inovasi olahan pangan berbahan lokal menjadi tiga produk unggulan baru berupa abon, siomay, dan dendeng sebagai penunjang daya tarik wisata sekaligus peluang usaha masyarakat. Hasil kegiatan menunjukkan peningkatan kemampuan Pokdarwis dalam merancang atraksi wisata budaya berbasis kearifan lokal yang lebih sistematis, menarik, dan memiliki nilai edukasi bagi pengunjung dengan indikator terukur yakni terciptanya travel pattern wisata budaya Desa Peniwen yang lebih efektif. Selain itu, masyarakat berhasil menghasilkan inovasi produk pangan lokal yang berpotensi dipasarkan sebagai oleh-oleh khas Desa Peniwen. Kegiatan ini tidak hanya memperkuat identitas budaya desa, tetapi juga membuka peluang diversifikasi ekonomi masyarakat melalui sinergi antara pariwisata budaya dan pengembangan produk lokal.